Disclosure of Governance, Ownership Structure, Earnings Quality, and Future Performance (Evidence from Indonesia and Singapore) - Imam Nurcahyo Fambudi; Etty Murwaningsari (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study analyzes the effect of institutional ownership structure and earnings quality on the future performance of companies with governance as a moderating variable in Indonesian and Singaporean companies. The company's future performance in general will usually be represented in the financial statements. Earnings quality is an important benchmark for companies to determine the quality of company accounting information. Institutional ownership is sharing ownership owned by an institution or business entity. Institutions here can mean ownership by banks, foundations, investment fund managers, pension fund managers, and others. Good Corporate Governance is corporate governance that explains the influence between various participants in the company that determines the direction of the company's future performance. The sample used in this study are companies listed on the Indonesia Stock Exchange and Singapore Stock Exchange from the period 2018 to 2020. This study uses a multiple linear regression model. The results show that institutional ownership structure has a significant positive effect on Future Performance and governance. as an independent variable shows a significant positive result on Future Performance.